Productivity improvement using overall equipment efficiency in semiconductor industry - Chinnappan, Ushananthini (2021)
As manufacturing has gone global and the market are getting more competitive every manufacturing facility must improve its process to remain competitive. To maintain and develop their ability to compete in a global market, production companies as an example semiconductor industry need to be effective in producing innovative and short lead times with high quality products and designing strong and flexible manufacturing system that provide the best preconditions for operational excellence. There are many approaches have been established to support the development of production processes, but Overall Equipment Efficiency (OEE) is the best practices to monitor and improve the production process. Therefore, OEE chosen as a viable approach for this project to calculate the competence of the production testers of XYMicroelectronics Sdn.Bhd.The OEE trends show that there are some issues and problems faced by the production that cause the operating testers do not achieve the targeted productivity level. It is identified that the OEE of test department drop due to the frequent downtime of the machines. Downtime is one of the biggest culprits for bringing down a plant’s OEE because it can take a huge of time out of our planned production time. This project is to identify the current performance and effectiveness of XYMicroelectronics Test Department production machines through OEE measurement. Other than that, this projects is also to identify the cause of tester downtimes during production and propose potential process improvement to increase the productivity and achieve production OEE target. Methodology planning was carried out to ensure that all the data and information collected during the data collection process was sufficient to satisfy the research objective requirements. By tracking machine performance, the OEE is used to calculate machine performance and increase the efficiency in terms of production output. At XYMicroelectronics the average value overall equipment effectiveness of the ETS 800 at Quarter 1 (Jan’20 – Mar’20) was 58.4% and Quarter 2 (Apr’20 – Jun’20) was 54.9%. During Quarter 3 (July’20 – Sept’20) efforts were made through the implementation of an effective strategy in the industry. The average value OEE of the ETS800 testing machine was increased from 54.9% to 68.8% through the implementation of proper training, planning production, 5S implementation, availability, better utilisation of resources, and raised employee morale and confidence. This implies a 13.9% increase in average OEE from before to after the implementation of continuous improvement. It is essential to reduce production losses and achieve greater competitiveness. Other than that, improvement in OEE will reduce the complex production problems into simple, accessible information that will make right decision and reduce operating expenses.